PENGGUNAAN UNITY ENGINE PADA PERANCANGAN GAME THE CIENT DENGAN NAVIGATION MESH - Riyadi Iskandar; Antonius Antonius; Edwinyo Edwinyo (INTEKSIS, 2021)
At present, the development of the gaming world is very rapid. This is reinforced by the source of newzoo.com which provides game development statistics from 2012 to 2019. These developments can not be denied anymore, because the game is indeed one of the hobbies that are most interested throughout the world. The development of existing games is not comparable with the mobile market that exists at the moment. This is evidenced in data from newzoo.com which contains that the sequence of platforms with the largest market currently is as much as 51% mobile, 25% console, and 24% PC. Data from wepc.com states that 53% of games are made for PC platforms, 37% of games are made for mobile platforms. The author uses a descriptive research design and research design in writing this study. The method of data collection used is by tracing the literature and articles that can be used as material to compile research. UML is used as a system analysis technique used to describe and document the design of game applications. C # programming language to do program code and apply navigation mesh. The resulting application is an offline survival horror game that uses a navigation mesh method with the Android platform. The conclusion of this study is that the application of the navigation mesh method is very supportive of the search path and for chasing and location of players. Suggestions from this research are that the addition of the FOV method for several monsters is needed so that the game challenges are more varied. Keywords: Games, Offline, Survivval Horror, Navigation Mesh, Android